Inhibition breast carcinogenesis via PI3K/AKT pathway using bioactive compounds of Strychnine tree (Strychnos nux-vomica): in silico study - Rispriandari, Aulia Ayu; Sarmoko, Sarmoko; Setyono, Joko; Wisesa, Sindhu (Universitas Ahmad Dahlan, 2024)
Breast cancer poses a significant global health challenge, with a notable prevalence in Indonesia. Given the intricate nature of breast cancer progression and classification, precise treatment strategies are imperative, particularly targeting signaling pathways like PI3K/AKT, pivotal in cell growth, proliferation, survival, and apoptosis. Bioactive compounds from the Strychnine tree demonstrate potential in enhancing apoptotic effects and inhibiting breast carcinogenesis. This potential is explored through in silico studies. This research aims to analyze potential targets of Strychnine tree compounds, along with binding energy and stability between ligands and receptors. Employing bioinformatics target analysis, molecular docking, and molecular dynamics simulation, the study reveals AKT1 as a potential target of Strychnine tree compounds. These compounds inhibit AKT1 at both active and allosteric sites, displaying notably low binding energy scores. For example, brucine exhibits a binding energy of -10.83 kJ/mol at the active site, surpassing the standard capivasertib. However, lupeol, with a binding energy of -11.14 kJ/mol, falls short of the MK-2206 standard at the allosteric site. Molecular dynamics simulations expose fluctuations in parameters like RMSD, RMSF, and binding energy within the initial 5 ns. In conclusion, Strychnine tree compounds, such as brucine and lupeol, showcase potential AKT1 inhibition at both active and allosteric sites, enhancing apoptotic effects. However, the stability of these compounds in binding to their receptors within the first 5 ns of the simulation warrants further investigation for prolonged interactions.